Fixed‐dose combination therapy for the prevention of atherosclerotic cardiovascular diseases - Bahiru, Ehete (Cochrane Database Syst Rev, 2017)
BACKGROUND: Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of death and disability worldwide, yet ASCVD risk factor control and secondary prevention rates remain low. A fixed‐dose combination of blood pressure‐ and cholesterol‐lowering and antiplatelet treatments into a single pill, or polypill, has been proposed as one strategy to reduce the global burden of ASCVD. OBJECTIVES: To determine the effect of fixed‐dose combination therapy on all‐cause mortality, fatal and non‐fatal ASCVD events, and adverse events. We also sought to determine the effect of fixed‐dose combination therapy on blood pressure, lipids, adherence, discontinuation rates, health‐related quality of life, and costs. SEARCH METHODS: We updated our previous searches in September 2016 of CENTRAL, MEDLINE, Embase, ISI Web of Science, and DARE, HTA, and HEED. We also searched two clinical trials registers in September 2016. We used no language restrictions. SELECTION CRITERIA: We included randomised controlled trials of a fixed‐dose combination therapy including at least one blood pressure‐lowering and one lipid‐lowering component versus usual care, placebo, or an active drug comparator for any treatment duration in adults 18 years old or older, with no restrictions on presence or absence of pre‐existing ASCVD. DATA COLLECTION AND ANALYSIS: Three review authors independently selected studies for inclusion and extracted the data for this update. We evaluated risk of bias using the Cochrane 'Risk of bias' assessment tool. We calculated risk ratios (RR) for dichotomous data and mean differences (MD) for continuous data with 95% confidence intervals (CI) using fixed‐effect models when heterogeneity was low (I(2) < 50%) and random‐effects models when heterogeneity was high (I(2) ≥ 50%). We used the GRADE approach to evaluate the quality of evidence. MAIN RESULTS: In the initial review, we identified nine randomised controlled trials with a total of 7047 participants and four additional trials (n = 2012 participants; mean age range 62 to 63 years; 30% to 37% women) were included in this update. Eight of the 13 trials evaluated the effects of fixed‐dose combination (FDC) therapy in populations without prevalent ASCVD, and the median follow‐up ranged from six weeks to 23 months. More recent trials were generally larger with longer follow‐up and lower risk of bias. The main risk of bias was related to lack of blinding of participants and personnel, which was inherent to the intervention. Compared with the comparator groups (placebo, usual care, or active drug comparator), the effects of the fixed‐dose combination treatment on mortality (FDC = 1.0% versus control = 1.0%, RR 1.10, 95% CI 0.64 to 1.89,  I(2) = 0%, 5 studies, N = 5300) and fatal and non‐fatal ASCVD events (FDC = 4.7% versus control = 3.7%, RR 1.26, 95% CI 0.95 to 1.66, I(2) = 0%, 6 studies, N = 4517) were uncertain (low‐quality evidence). The low event rates for these outcomes and indirectness of evidence for comparing fixed‐dose combination to usual care versus individual drugs suggest that these results should be viewed with caution. Adverse events were common in both the intervention (32%) and comparator (27%) groups, with participants randomised to fixed‐dose combination therapy being 16% (RR 1.16, 95% CI 1.09 to 1.25, 11 studies, 6906 participants, moderate‐quality evidence) more likely to report an adverse event . The mean differences in systolic blood pressure between the intervention and control arms was ‐6.34 mmHg (95% CI ‐9.03 to ‐3.64, 13 trials, 7638 participants, moderate‐quality evidence). The mean differences (95% CI) in total and LDL cholesterol between the intervention and control arms were ‐0.61 mmol/L (95% CI ‐0.88 to ‐0.35, 11 trials, 6565 participants, low‐quality evidence) and ‐0.70 mmol/L (95% CI ‐0.98 to ‐0.41, 12 trials, 7153 participants, moderate‐quality evidence), respectively. There was a high degree of statistical heterogeneity in comparisons of blood pressure and lipids (I(2) ≥ 80% for all) that could not be explained, so these results should be viewed with caution. Fixed‐dose combination therapy improved adherence to a multidrug strategy by 44% (26% to 65%) compared with usual care (4 trials, 3835 participants, moderate‐quality evidence). AUTHORS' CONCLUSIONS: The effects of fixed‐dose combination therapy on all‐cause mortality or ASCVD events are uncertain. A limited number of trials reported these outcomes, and the included trials were primarily designed to observe changes in ASCVD risk factor levels rather than clinical events, which may partially explain the observed differences in risk factors that were not translated into differences in clinical outcomes among the included trials. Fixed‐dose combination therapy is associated with modest increases in adverse events compared with placebo, active comparator, or usual care but may be associated with improved adherence to a multidrug regimen. Ongoing, longer‐term trials of fixed‐dose combination therapy will help demonstrate whether short‐term changes in risk factors might be maintained and lead to expected differences in clinical events based on these changes.